Challenges of LSPB contract strategy in brownfield projects for the oil and gas industry: a case for adaptability in bulk plant developments - Alwossabee, Abdulatif; Al-Qahtani , Musaab (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This paper explores the limitations of employing Lump Sum Procure and Build (LSPB) contracts in brownfield oil and gas projects, particularly within bulk plant developments. While LSPB contracts offer cost predictability and defined deliverables, their rigid structure often proves unsuitable for the dynamic and complex nature of brownfield environments. Challenges such as scope uncertainty, late vendor input, unforeseen site conditions, and the integration of evolving digital systems frequently lead to delays, cost overruns, and disputes. This paper highlights how the traditional waterfall project execution model, commonly used in LSPB contracts, struggles to accommodate the iterative design and real-time adjustments necessary in operational facilities. To address these shortcomings, the paper proposes several adaptive strategies, including hybrid contract models, early vendor involvement, phased execution, and performance-based contracting. These approaches aim to enhance flexibility, reduce risk, and improve collaboration between stakeholders. By integrating best practices from project management and construction industry research, the paper advocates for a more adaptable and outcome-focused contracting strategy tailored to the unique demands of brownfield developments in the oil and gas sector.